Neurocognitive deficits in shy college students: An event-related potential analysis of the P3 component evoked by evaluations of others. (1st February 2019) - Yang, Yu; Hong, Sun; Fengqiang, Gao; Lei, Han
Abstract: Related research has reported that because shy individuals are extremely self-consciousness, they hold the evaluations of others to be highly relevant. However, cognitive neuroscientific evidence for this conclusion is limited. In the present study, a real-life evaluation circumstance was established in which evaluative comments about college students and their friends were collected. EEG signals of shy and non-shy college students were recorded while they were instructed to judge whether these comments were suitable for evaluating themselves (self-related task) and their friends (friend-related task) and to indicate whether they knew the meaning of the adjectives (baseline task). Shy subjects demonstrated a significantly larger P3 mean amplitude for both self-related and friend-related tasks compared with the baseline task. By contrast, non-shy subjects demonstrated a significantly larger P3 mean amplitude in the self-related task than in the other two tasks. The baseline task results were then subtracted, and the difference in EEG signals revealed that shy subjects were more sensitive to comments about themselves as well as their friends compared with their non-shy counterparts. These findings provide neurophysiological evidence for the interpersonal evaluation sensitivity of shy individuals in the late attention-sensitive stage. Furthermore, excessive involvement in interpersonal evaluations may be a neurocognitive deficit in shy individuals, which may be related to maladaptative cognition.